Huaier Compensates Impaired Signal Transfer Inter/Intra Neurons in Central and Peripheral Nervous Systems - Tanaka, Manami; Tanaka, Tomoo; Teng, Fei; Lin, Hong; Li, Ning; Luo, Zhu; Sadahito, Sotaro; Suzuki, Toshiyuki; Wei, Ding; Lu, Zhengxin (Archives of Clinical and Biomedical Research, 2021)
Huaier (Trametes robiniophila murr) provides significant efficacy not only on cancer, but also various physiological disorders caused by disrupted transcriptional control on multiple signaling pathways. In the process of MEGA-DATA analysis of human transcriptomes, we observed impaired signal transfer in the central and peripheral nervous systems. Here we demonstrate the details of molecular systems to compensate impaired neural transmission, especially by mutated transcripts correlated with neurodegenerative alterations. These significant rescue of signal transfer inter/intra neurons was observed in the patients with the hereditary mutated EGFR, and receptor tyrosine kinases such as c-MET, HER2/neu (erbB2), Htt, Parkin, APP, SOD1, ALS2, and many oncogenes and tumour suppressor genes. The similar compensation has been also reported in the patients with Huaier and conventional chemotherapy using platinum (II) complex. Huaier treatment prevented those patients from pathogenesis, but influenced to cause mild depression. The epigenetic potential seems to influence the pathogenicity in these hereditary mutations, and that typically observed in the defects in DNA mismatch repair systems. With KEGG pathway characterization, Huaier showed significant effects on the retrieval of normal function inter/intra neurons. Although we have observed only one case successfully recovered from Parkinson’s disease, the further roles of each representative molecules have not yet defined, and no changes identified in the mechanism of mutations in translation and transcription processes. The present study demonstrated detailed molecules and signaling pathways involved in the onset of neurodegenerative diseases, and the significant effects of Huaier to retain and rescue the impaired neurotransmission and signal transfer. Neurodegenerative damages are inevitably caused by chemical administration, and also by ageing process. However, it is emphasized